Obligation to Learn and Search Science from the Perspective of the Prophet's Hadits - Abid Nurhuda (PT Publikasiku Academic Solution, 2023)
Knowledge is something that is needed by humans to achieve happiness in the world and the hereafter. And there is no other way to acquire this knowledge except by studying and hunting for it. Besides that, the owner gets his position and priority in the eyes of Allah SWT so that the Prophet obliges his people to study and seek knowledge through his words. So the purpose of this study is to describe the Obligation to Study and Seek Knowledge from the Perspective of the Prophet's Hadith. The method used is qualitative with a literature study approach, while the sources of data collected come from primary and secondary data and then the contents are analyzed and finally concluded descriptively. The results of the study show that the Obligation to Study and Seek Knowledge from the Perspective of the Prophet's Hadith includes the Hadith of Bukhari No. 73 which contains the permissibility of hasad towards knowledgeable people, practicing and teaching others. Then Sunan Ibnu Majah Hadith No. 224 contains obligations for every Muslim wherever and whenever without any restrictions. And finally, Muttafaq A'laih (Bukhari Hadith No. 100 and Muslim Hadith No. 2673) contains a warning to the people of the Prophet Muhammad that knowledge will be withdrawn slowly from its owner, therefore every Muslim is required to study to minimize the appointment of leaders/imams from ignorant people uneducated.